Synthesis and crystal structure of 2-azido-N-(4-nitrophenyl)acetamide, C8H7N5O3 - Missioui Mohcine; Guerrab Walid; Mague Joel T.; Ramli Youssef (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C8H7N5O3, monoclinic, P21/n (no. 14), a = 5.0340(2) Å, b = 21.1023(9) Å, c = 9.2880(4) Å, β = 94.909(1)°, V = 983.04(7) Å3, Z = 4, Rgt(F) = 0.0470, wRref(F2) = 0.1496, T = 298(2) K.